POST-HARVEST DISEASES IN INDRALAYA DISTRICT, SOUTH SUMATRA - Rahmat Pratama; Ayu Safitri (BIOVALENTIA: Biological Research Journal, 2022)
The agricultural sector, especially in Indonesia, is always faced with problems from various factors that can reduce the productivity of a plant. One of these factors is the presence of attacks from plant-disturbing organisms. The method used in this research is by using a purposive sampling method. Samples of diseased plants were observed and taken for observation in the Phytopathology Laboratory, Plant Protection Study Program, Faculty of Agriculture, Sriwijaya University. From the observations that have been made, it was found that many chili plants were attacked by Colletotrichum Rot disease Erwinia caratovora in carrots, anthracnose in oranges and bananas, anthracnose in mangoes, and papayas. Many postharvest diseases found in plants in Indralaya are caused by pathogens in the form of fungi and bacteria.